Biological Impact of Transpulmonary Driving Pressure in Experimental Acute Respiratory Distress Syndrome. (August 2015) - Samary, Cynthia S.; Santos, Raquel S.; Santos, Cíntia L.; Felix, Nathane S.; Bentes, Maira; Barboza, Thiago; Capelozzi, Vera L.; Morales, Marcelo M.; Garcia, Cristiane S. N. B.; Souza, Sergio A. L.; Marini, John J.; Gama de Abreu, Marcelo; et al.
<x xml:space="preserve">Abstract</x> Background: Ventilator-induced lung injury has been attributed to the interaction of several factors: tidal volume (VT), positive end-expiratory pressure (PEEP), transpulmonary driving pressure (difference between transpulmonary pressure at end-inspiration and end-expiration, ΔP, L), and respiratory system plateau pressure (Pplat, rs). Methods: Forty-eight Wistar rats received Escherichia coli lipopolysaccharide intratracheally. After 24 h, animals were randomized into combinations of VT and PEEP, yielding three different ΔP, L levels: ΔP, LLOW (VT = 6 ml/kg, PEEP = 3 cm H2O); ΔP, LMEAN (VT = 13 ml/kg, PEEP = 3 cm H2O or VT = 6 ml/kg, PEEP = 9.5 cm H2O); and ΔP, LHIGH (VT = 22 ml/kg, PEEP = 3 cm H2O or VT = 6 ml/kg, PEEP = 11 cm H2O). In other groups, at low VT, PEEP was adjusted to obtain a Pplat, rs similar to that achieved with ΔP, LMEAN and ΔP, LHIGH at high VT. Results: At ΔP, LLOW, expressions of interleukin (IL)-6, receptor for advanced glycation end products (RAGE), and amphiregulin were reduced, despite morphometric evidence of alveolar collapse. At ΔP, LHIGH (VT = 6 ml/kg and PEEP = 11 cm H2O), lungs were fully open and IL-6 and RAGE were reduced compared with ΔP, LMEAN (27.4 ± 12.9 vs. 41.6 ± 14.1 and 0.6 ± 0.2 vs. 1.4 ± 0.3, respectively), despite increased hyperinflation and amphiregulin expression. At ΔP, LMEAN (VT = 6 ml/kg and PEEP = 9.5 cm H2O), when PEEP was not high enough to keep lungs open, IL-6, RAGE, and amphiregulin expression increased compared with ΔP, LLOW (41.6 ± 14.1 vs. 9.0 ± 9.8, 1.4 ± 0.3 vs. 0.6 ± 0.2, and 6.7 ± 0.8 vs. 2.2 ± 1.0, respectively). At Pplat, rs similar to that achieved with ΔP, LMEAN and ΔP, LHIGH, higher VT and lower PEEP reduced IL-6 and RAGE expression. Conclusion: In the acute respiratory distress syndrome model used in this experiment, two strategies minimized ventilator-induced lung injury: (1) low VT and PEEP, yielding low ΔP, L and Pplat, rs; and (2) low VT associated with a PEEP level sufficient to keep the lungs open.